Peter y Pan - Muñoz Corcuera, Alfonso (Cuadernos de Filología Clásica. Estudios Latinos, 2009)
The figure of the god Pan was the object of a special attention during the period that goes from 1890 to 1926 in the English literature. Partial consequence of this situation was the creation of one of the most important characters of the 20th century literature, Peter Pan, question that has been ignored by the academic world almost completely. This article proposes to attend to the importance of the mythological model in the character created by James Matthew Barrie in 1902.
Keywords: Pan; Peter Pan; Classical tradition; English literature; Children literature